FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU IBU DALAM PEMBERIAN ASI EKSKLUSIF: STUDY LITERATURE REVIEW - Wardhani, Febby Kusuma; Wijayanti, Kartika; Hidayah, Nurul (Prosiding University Research Colloquium, 2022)
Background : Mother's milk (ASI) is the most perfect food source for babies because it contains various substances and antibodies that are important for the growth and development of babies. Breastfeeding means providing nutrients with high nutritional value needed for growth and development of nerves and brain, providing immunity against several diseases and creating emotional bonds between mother and baby. The problem of giving breast milk (ASI) to babies deserves serious attention from the government and the community, and the ineffectiveness of exclusive breastfeeding can cause nutritional disorders. The low coverage of exclusive breastfeeding is caused by mothers who work outside the home and lack of knowledge on how to give exclusive breastfeeding to babies. Exclusive breastfeeding behavior can also be influenced by the so-called facilitation factors (education, knowledge, age, occupation, number of children and breastfeeding experience), supporting factors (family income, availability of time and maternal health), and driving factors (family support). and health worker support). Objective: The general purpose of this literature review is to determine the factors that influence the behavior of mothers in exclusive breastfeeding. Methods: The method used in this study is a literature review design, article searches using a database from a journal, namely Google Scholar. A total of 13 articles met the inclusion criteria. The total sample used in 13 articles is 1310 respondents. The sampling technique in this research is Cross Sectional. Results: The results of the literature review obtained nine factors that influence the behavior of mothers in exclusive breastfeeding, including: knowledge, education, attitudes, facilities and infrastructure, family support, work, values and culture, motivation and husband's support. Conclusion: Of the nine factors that most influence the behavior of mothers in exclusive breastfeeding, among others: knowledge, education, attitudes, facilities and infrastructure, family support, and work.